Evaluation of the Antimicrobial Ability of Probiotics Against Nosocomial Infections by Inhibiting Ompa Gene Expression in Acinetobacter Baumannii - Farangis Ghanipour; Razieh Nazari; Seyed Soheil Aghaee; Parvane Jafari (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk, 2021)
Background: and Aim Acinetobacter baumannii causes various nosocomial infections and has a high antibiotic resistance. Probiotics can produce metabolites with antimicrobial properties. This study aims to evaluate the antimicrobial ability of probiotics against nosocomial pathogens by inhibiting the ompA gene expression effective in biofilm formation in Acinetobacter baumannii. Methods & Materials: The antimicrobial properties of probiotics against nosocomial pathogens were evaluated phenotypically. The polymerase chain reaction (PCR) technique was used to identify the ompA gene in Acinetobacter baumannii. After treatment with Bacillus licheniformis supernatant, the ompA gene expression was compared before and after treatment with real-time PCR technique. Ethical Considerations This study was approved by the ethics committee of Islamic Azad University, Qom branch (Code: IR.IAU.QOM.REC.1398.004). Results: Among the study probiotics, Bacillus licheniformis supernatant had the best antimicrobial properties against nosocomial isolates of Acinetobacter baumannii A52, Acinetobacter baumannii ATCC19606, Kelebsiella pneumonia ATCC70063, and Pseudomonas aeruginosa PAO1. Bacillus licheniformis supernatant also significantly reduced the biofilm formation and ompA gene expression in Acinetobacter baumannii. Conclusion: Bacillus licheniformis can produce substances with antimicrobial and antibiofilm properties. It can be used for controlling the causative agents of nosocomial infections.